The Symbolic Meaning of Ubo Rampe in the Traditional Grebeg Pasa Ceremony at Kasunanan Surakarta Hadiningrat Palace - Candraderi Christmatara; Nurhayati Nurhayati (Javanologi: International Journal of Javanese Studies, 2025)
This study aims to reveal the lexical meaning, cultural meaning, and human relationships in cultural practices within the Grebeg Pasa Ceremony at the Kasunanan Surakarta Hadiningrat Palace. This research employs a qualitative descriptive method. The data sources were obtained through interviews with abdidalem (royal servants) of the Kasunanan Surakarta Hadiningrat Palace. Data collection techniques included observation and interviews. The analysis was conducted using content analysis techniques. The results of this study indicate that 22 components of ubo rampe, each carrying lexical and cultural meanings. In addition, ubo rampe also reflects four types of human relationships in culture. This research has implications for cultural studies or cultural preservation in order to uncover the hidden message of traditional ceremonies.